2017
DOI: 10.1111/jep.12840
|View full text |Cite
|
Sign up to set email alerts
|

What does physicians' clinical expertise contribute to oncologic decision‐making? A qualitative interview study

Abstract: Using measurable knowledge and adherence to standards as indicators does not account for the complexity of clinical expertise. Other factors, such as the importance of bodily experience and physicians' intuitive knowledge, must be considered, also with respect to the occurrence of treatment biases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Despite the ability to register clinical findings correctly, these must be combined with the appropriate imaging and other diagnostic tools to allow a correct diagnosis and treatment plan. Salloch and coworkers [ 29 ] have recently stressed the importance of the physician's expertise to find appropriate diagnoses and treatment plans for each patient in oncologic decision-making. Registration of pathology in the TMJ, including jaw movements, muscle palpation, and TMJ noises, may be seen either independently or in combination with TMDs such as myalgia, disc derangement, or inflammatory joint diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the ability to register clinical findings correctly, these must be combined with the appropriate imaging and other diagnostic tools to allow a correct diagnosis and treatment plan. Salloch and coworkers [ 29 ] have recently stressed the importance of the physician's expertise to find appropriate diagnoses and treatment plans for each patient in oncologic decision-making. Registration of pathology in the TMJ, including jaw movements, muscle palpation, and TMJ noises, may be seen either independently or in combination with TMDs such as myalgia, disc derangement, or inflammatory joint diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There are some clinical and technical criteria to guide decisions at the EoL, but the patient’s situation around the time of death is so particular to personal circumstances that decisions are mostly guided by clinical judgement and prior expertise [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on diagnostic error provides insight into how clinicians make decisions in relation to patient treatment. It suggests decision makers tend to rely on heuristics, tacit knowledge, and contextual experience when making complex decisions . In the context of intensive care, studies have shown clinicians' predictions of poor outcome for certain patient groups to be unreliable when they rely on their clinical assessment over objective measurements, suggesting an element of cognitive bias .…”
Section: Discussionmentioning
confidence: 99%